Revision of Ephydrini Zetterstedt (Diptera: Ephydridae) from the Americas south of the United States - Mathis, Wayne N.; Marinoni, Luciane (Zootaxa, 2016)
The Neotropical genera and species of the tribe Ephydrini are revised and include nine genera and 33 species. Of the nine genera, Setacera Cresson, Cirrula Cresson, Dimecoenia Cresson, Paracoenia Cresson and Ephydra Fallén are mostly temperate in distribution, primarily in the Northern Hemisphere. The other four genera, which are exclusively Neotropical, include two, Austrocoenia and Notiocoenia, that were treated previously in the tribe Scatellini, and two recently described genera: Paraephydra (type species: Paraephydra freitasi (Oliveira)) and Neoephydra (type species: Neoephydra araucaria Mathis). New species described herein are: Neoephydra neotropica (Chile), N. dasycephala (Argentina and Peru), N. mallonota (Argentina, Bolivia, and Chile), N. shewelli (Argentina, Bolivia, and Chile), N. inca (Argentina, Bolivia, Peru), N. penai (Chile) and N. trichina (Argentina and Chile). New synonyms are (cited in their original combinations): Ephydra densepilosa Hendel = E. ciligena Rondani, Dimecoenia grumanni Oliveira = E. ciligena Rondani, D. coltaensis Cresson = D. zurcheri Hendel, D. carrerai Oliveira = D. zurcheri Hendel, D. lopesi = E. ciligena Rondani, D. travassosi Mello and Oliveira = E. prionoptera Thomson. A neotype is designated for E. caesia Wulp, and the following lectotype designations have also been made to better stabilize nomenclature (here cited in their original combination): Ephydra chilensis Macquart, Ephydra densepilosa Hendel, Ephydra pravoneura Hendel, Ephydra prionoptera Thomson, and Dimecoenia zurcheri Hendel. Dimecoenia venteli Oliveira is listed as a species inquirenda, as the type series includes only female specimens that we cannot presently recognize. Although the genera and subgenera are fairly easily distinguished, the included species are frequently difficult to separate, and we have generally relied on characters of the male terminalia to determine a species identity. Illustrations of male terminalia and distribution maps are included for each species and keys to all taxa have been provided.